Juhūd al-Maṭbaʻah al-ʻArabīyah li-Abī al-Yaqẓān fī Iḥyāʼ al-Turāth al-Islāmī bi-al-Jazāʼir - Aḥmad, ʻAbdalī (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Shaykh Ibrāhīm ibn ʿĪsá Ḥamdī Abū al-Yaqẓān (1888–1973), the Mizabi Ibāḍī, was among the leading figures of the reform movement in Algeria in the period between 1920 and 1962. He was a man of letters and a poet, an eloquent orator and an accomplished journalist titled the dean of the Algerian press, and a memoriser of the Book of God — no surprise, since he was a descendant of the scholarship of Mzab through Shaykh Aṭfayyish. These are qualities rarely combined except in scholars of his kind. He believed in the cause of his country, Algeria, then groaning under French colonial rule, which imposed upon it a cultural and doctrinal war intended to cut it off from its civilizational and religious belonging. The coloniser naturally monopolised and forbade all the instruments and means of cultural work and constrained them, and this paper examines how, against that constraint, Abū al-Yaqẓān's Arabic press served the revival of the Islamic heritage.
MHF-PRINT2018-012
Keywords: Abū al-Yaqẓān; Algerian press; Islamic heritage; Ibāḍī studies; Colonial Algeria; Printing history